Conventional Traders' Survival Strategies in the Middle of Online Shop Development (Case Study of Clothing Selling) - Mohamad Khairi; Abdul Rahman (metromedia.education, 2022)
Currently internet users are increasing. Starting from parents to teenagers use the internet. The use of the internet is not only carried out by the upper levels of society. All levels of society can now access the internet easily and at affordable prices. The development of the internet has created a new lifestyle for people. People choose to do all activities using the internet, including shopping. Nowadays people prefer online shopping instead of coming directly to the store. This lifestyle change has an impact on conventional traders. The existence of conventional traders is starting to be threatened in the midst of the rise of online traders. To anticipate this, conventional traders need to implement survival strategies that can maintain their business continuity. The strategy carried out is related to product, price, and location aspects. This competitive strategy is carried out in accordance with local conditions and current developments. Suggestions that can be given to conventional traders need to increase their social capital. Having strong social capital can create an advantage over online shopping. Product prices can also compete with online stores that are considered to have low prices. Without having to give more discounts, ordinary conventional traders compete.